Effects Of Intermetallic Growth And Bonding Parameters On Wire- Bond Strength For Gold - Aluminium System - Chan, Sook Chien (2002)
The effect of gold -aluminum intermetallic growth at elevated temperatures on bond shear strength is studied. A diffusion model is derived from the Fick's first law for verifying with the measurement of gold-aluminum diffusion reaction rate.